Pemberdayaan Perempuan melalui Program Desa Damai Wahid Foundation di Kelurahan Pengasinan Kota Depok - Aini, Mutia; Tasman, Tasman (Dakwah: Jurnal Kajian Dakwah dan Kemasyarakatan, 2024)
Women are important actors in creating inclusive peace. However, the potential and contribution of women in peace is often ignored. Women are also a vulnerable group in conflicts of intolerance and violent extremism. Based on this, the Wahid Foundation, supported by United Nations Women, created the Peaceful Village program by approaching it through women's empowerment. The aim of this research is to describe the results of women's empowerment carried out by the Damai Pengasinan Village under the guidance of the Wahid Foundation. This research uses a qualitative research approach with descriptive research type. Data collection techniques in this research used observation, interview and documentation study techniques. The results of this research show that the results of empowerment, namely increasing income, increasing insight, critical awareness for handling conflict resolution, and the benefits of women's participation in development at the sub-district level can be felt by women in the Pengasinan sub-district, Depok City.